Electrolyte for secondary battery and lithium secondary battery including same

By adding specific polymers to the electrolyte of the lithium secondary battery to form a stable film, the problem of transition metal ions dissolution in the lithium secondary battery is solved, the low-temperature resistance and high-temperature durability of the battery are improved, and a longer service life and higher safety are achieved.

CN119816977APending Publication Date: 2025-04-11LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380057473.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-02
Filing Date
2023-08-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The liquid electrolytes of existing lithium secondary batteries have low stability during charging and discharging, and are susceptible to volatility of organic solvents, resulting in gas production, pressure increase, structural deformation, and even explosion inside the battery. Meanwhile, dissolution and deposition of transition metal ions reduces the stability of the electrode and the capacity of the battery.

Method used

Using an electrolyte including a lithium salt, a non-aqueous organic solvent and a polymer, the polymer consists of repeating units derived from specific monomers, which can form a stable film on the surface of the positive electrode, inhibit the dissolution of transition metal ions, and improve the low-temperature resistance and high-temperature durability of the electrolyte.

Benefits of technology

By forming a stable film, the low-temperature resistance and high-temperature durability of the lithium secondary battery are improved, side reactions and dissolution of metal ions are reduced, the service life of the battery is extended and safety is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005260037510000031
    Figure BDA0005260037510000031
  • Figure BDA0005260037510000032
    Figure BDA0005260037510000032
  • Figure BDA0005260037510000041
    Figure BDA0005260037510000041
Patent Text Reader

Abstract

The present disclosure relates to an electrolyte for a secondary battery, and a lithium secondary battery including the same. The electrolyte for a secondary battery according to the present disclosure may include a lithium salt, a non-aqueous organic solvent, and a polymer as an additive, the polymer including a repeating unit derived from a monomer represented by Formula 1 and a repeating unit derived from a monomer represented by Formula 2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to Korean Patent Application No. 10-2022-0097614 filed on August 4, 2022 and Korean Patent Application No. 10-2023-0101238 filed on August 2, 2023, the disclosures of which are incorporated herein by reference in their entirety. Technical Field

[0004] The present disclosure relates to an electrolyte for a secondary battery and a lithium secondary battery including the same. More specifically, the present disclosure relates to an electrolyte for a secondary battery capable of inhibiting dissolution of a transition metal by forming a polymer film on an electrode surface, and a lithium secondary battery including the same. Background Art

[0005] Recently, with the rapid development of the power, electronics, communications, and computer industries, the demand for high-performance, high-stability secondary batteries has been growing. In particular, thin-film and miniaturized lithium secondary batteries, which are core components in this field, need to meet the trend of miniaturization and lightweighting of electronic and communication equipment.

[0006] Liquid electrolytes, such as ion-conductive organic liquid electrolytes in which salts are dissolved in organic solvents using carbonate organic solvents as main solvents, have been widely used as electrolytes for lithium secondary batteries. However, the disadvantage of this liquid electrolyte is that it is not only extremely susceptible to the volatilization of organic solvents, but also has low stability, because gas is generated inside the battery due to the decomposition of carbonate organic solvents and / or the side reactions between organic solvents and electrodes during the charging and discharging process, resulting in expansion of the battery thickness. In particular, this side reaction may be accelerated during storage at high temperatures. This continuously generated gas causes the internal pressure of the battery to increase, resulting in the phenomenon of deformation or explosion of the center of a specific surface of the battery, such as prismatic batteries expanding in a specific direction, etc. This also leads to local differences in the adhesion of the electrode surface in the battery, which causes the problem that the electrode reaction cannot occur in the same way on the entire electrode surface.

[0007] Therefore, in order to ensure the stability of lithium secondary batteries, various additives that can provide various functions to the electrolyte have recently been studied.

[0008] The passivation film on the surface of the positive electrode is corroded by repeated charging and discharging processes, moisture inside the battery cell, Lewis acid, etc., which can cause the structural stability of the positive electrode to decrease as the transition metal ions are dissolved from the positive electrode. In addition, the dissolved transition metal ions are electro-deposited on the negative electrode or precipitated from the negative electrode, reducing the passivation ability of the solid electrolyte interface (SEI), and therefore, there is a problem of negative electrode degradation. This deterioration phenomenon of the negative electrode promotes the decomposition of the electrolyte solvent, accelerates the generation of gas, and leads to side reactions such as the desorption of lithium ions inserted into the negative electrode, thereby causing a decrease in battery capacity.

[0009] Therefore, it is necessary to develop an electrolyte that can form a stable film with low interfacial resistance and high ion transfer efficiency on the positive electrode surface and has stable passivation ability to inhibit the dissolution of transition metals. Summary of the invention

[0010] Technical issues

[0011] To solve the above problems, the present invention aims to provide an electrolyte for a secondary battery capable of forming a film having low interface resistance and stable passivation ability on the surface of a positive electrode.

[0012] Furthermore, the present disclosure also aims to provide a lithium secondary battery having improved low-temperature resistance properties and high high-temperature durability by including the electrolyte for a secondary battery of the present disclosure.

[0013] Technical Solution

[0014] To achieve the above objectives, in one embodiment of the present disclosure, there is provided an electrolyte for a secondary battery, comprising:

[0015] a lithium salt; a nonaqueous organic solvent; and a polymer as an additive, the polymer including a repeating unit derived from a monomer represented by Formula 1 and a repeating unit derived from a monomer represented by Formula 2.

[0016] [Formula 1]

[0017]

[0018] In formula 1,

[0019] R is an alkylene group having 1 to 5 carbon atoms, and

[0020] R" is H or Li.

[0021] [Formula 2]

[0022]

[0023] In formula 2,

[0024] R 1 and R 2 Each is independently an alkylene group having 1 to 5 carbon atoms.

[0025] The lithium salt may include LiPF 6 and may further include at least one selected from the following lithium salts: LiCl, LiBr, LiI, LiBF 4 、LiClO 4 , LiB 10 Cl 10 、LiAlCl 4 、LiAlO 4 、LiCF 3 SO 3 、LiCH 3 CO 2 、LiCF 3 CO 2 、LiAsF 6 、LiSbF 6 、LiCH 3 SO 3 、LiTFSI(lithium(bis)trifluoromethanesulfonimide,LiN(SO 2 CF 3 ) 2 )、LiFSI(Lithium bis(fluorosulfonyl)imide,LiN(SO 2 F) 2 )) or LiBETI (lithium bisperfluoroethanesulfonimide, LiN(SO 2 CF 2 CF 3 ) 2 )).

[0026] In Formula 1, R may be an alkylene group having 1 to 4 carbon atoms, and R″ may be H. Specifically, R may be an alkylene group having 1 to 3 carbon atoms, and preferably, R may be an alkylene group having 1 carbon atom or 2 carbon atoms.

[0027] In addition, in Formula 2, R 1 and R 2 The groups may each independently be an alkylene group having 1 to 4 carbon atoms, and specifically, may be an alkylene group having 2 or 3 carbon atoms.

[0028] The polymer may further include a repeating unit derived from a monomer represented by Formula 3 below.

[0029] [Formula 3]

[0030]

[0031] In formula 3,

[0032] R' is an alkyl group having 1 to 6 carbon atoms.

[0033] In Formula 3, R′ may be an alkyl group having 1 to 5 carbon atoms, and preferably may be an alkyl group having 1 to 4 carbon atoms.

[0034] The polymer may further include a unit represented by Formula 4 below.

[0035] [Formula 4]

[0036]

[0037] In formula 4,

[0038] R, R 1 and R 2 are each independently an alkylene group having 1 to 5 carbon atoms,

[0039] R' is an alkyl group having 1 to 6 carbon atoms,

[0040] R" is H or Li,

[0041] k is any integer from 1 to 15,000,

[0042] m is any integer from 10 to 12,000, and

[0043] n is an arbitrary integer from 10 to 8,500.

[0044] According to another embodiment of the present disclosure, the present disclosure provides a lithium secondary battery including the electrolyte for a secondary battery of the present disclosure.

[0045] Beneficial Effects

[0046] The electrolyte for a secondary battery of the present disclosure can form a film having stable passivation capability and low interface resistance on the positive electrode surface by including a polymer containing a cyano group as a thermally polymerizable functional group at its end as an additive. Therefore, a lithium secondary battery including the electrolyte can achieve the effect of improving low-temperature resistance properties while having excellent high-temperature durability. DETAILED DESCRIPTION

[0047] Hereinafter, the present invention will be described in more detail.

[0048] It is to be understood that the words or terms used in the specification and claims should not be interpreted as the meanings defined in general dictionaries, and it is to be further understood that, based on the principle that the inventor can appropriately define the meanings of words or terms to best interpret the invention, these words or terms are interpreted as having meanings consistent with their meanings in the context of the relevant technical field and the technical concept of the invention.

[0049] In the present specification, the expression "*" indicates the same or different atoms or moieties connected between the ends of a formula, unless otherwise specifically stated.

[0050] In addition, in this specification, the expression "alkylene group" means a straight or branched divalent saturated hydrocarbon group. In one embodiment, the alkylene group may be substituted or unsubstituted. The alkylene group includes methylene, ethylene, propylene, isopropylene, butane, isobutylene, tert-butylene, pentane, and 3-pentane, but the alkylene group is not limited thereto.

[0051] Furthermore, in the present specification, the expression "repeating unit" means a monomer unit constituting a polymer.

[0052] Furthermore, in the present specification, the expression "thermally polymerizable functional group" means a functional group capable of undergoing polymerization between the same functional group or different functional groups by heating without a polymerization initiator.

[0053] In addition, unless otherwise defined in the present specification, the expression "substituted" means that at least one hydrogen bonded to carbon is substituted with an element or group other than hydrogen, for example, an alkyl group having 1 to 5 carbon atoms.

[0054] Electrolytes for secondary batteries

[0055] Specifically, in one embodiment of the present disclosure, there is provided an electrolyte for a secondary battery, comprising:

[0056] lithium salt; non-aqueous organic solvent; and

[0057] As a polymer of the additive, the polymer includes a repeating unit derived from the monomer represented by Formula 1 and a repeating unit derived from the monomer represented by Formula 2.

[0058] [Formula 1]

[0059]

[0060] In formula 1,

[0061] R is an alkylene group having 1 to 5 carbon atoms, and

[0062] R" is H or Li.

[0063] [Formula 2]

[0064]

[0065] In formula 2,

[0066] R 1 and R 2 Each is independently an alkylene group having 1 to 5 carbon atoms.

[0067] (1) Lithium salt

[0068] First, the electrolyte for a secondary battery of the present disclosure includes at least one lithium salt.

[0069] The lithium salt may be used without limitation as long as it is a compound that can provide lithium ions. For example, the lithium salt may include Li + as cations, and may include a selection of F - , Cl - Br - ,I - 、NO 3 - 、N(CN) 2 - , BF 4 - , ClO 4 - , B 10 Cl 10 - 、AlCl 4 - 、AlO 4 - CF 3 SO 3 - , CH 3 CO 2 - CF 3 CO 2 - , AsF 6 - , SbF 6 - , CH 3 SO 3 - ,(CF 3 CF 2 SO 2 ) 2 N - ,(CF 3 SO 2 ) 2 N - 、(FSO2 ) 2 N - , BF 2 C 2 O 4 - , B.C. 4 O 8 - PF 4 C 2 O 4 - PF 2 C 4 O 8 - ,(CF 3 ) 2 PF 4 - ,(CF 3 ) 3 PF 3 - ,(CF 3 ) 4 PF 2 - ,(CF 3 ) 5 PF - ,(CF 3 ) 6 P - , C 4 F 9 SO 3 - CF 3 CF 2 SO 3 - CF 3 CF 2 (CF 3 ) 2 CO - ,(CF 3 SO 2 ) 2 CH - CF 3 (CF 2 ) 7 SO 3 - , C 6 HF 6 N - (LiTDI), or SCN - as an anion.

[0070] Specifically, the lithium salt may include LiPF 6 As a typical example.

[0071] In addition, the lithium salt may include LiPF 6 As the first lithium salt, the salt is selected from the group consisting of excluding LiPF 6 LiCl, LiBr, LiI, LiBF 4 、LiClO 4 , LiB 10 Cl 10 、LiAlCl 4 、LiAlO 4 、LiCF 3 SO 3 、LiCH 3 CO 2 、LiCF 3 CO 2 、LiAsF 6 、LiSbF 6 、LiCH 3 SO 3 、LiTFSI(lithium(bis)trifluoromethanesulfonimide,LiN(SO 2 F 3 ) 2 )、LiFSI(Lithium bis(fluorosulfony1)imide, LiN(SO 2 F) 2 ) or LiBETI (lithium bisperfluoroethanesulfonimide, LiN(SO 2 CF 2 CF 3 ) 2 ) as the second lithium salt.

[0072] When two types of lithium salts are included as the lithium salt, a molar ratio of the first lithium salt to the second lithium salt is 1:0.01 to 1:50, specifically 1:1 to 1:30, and more specifically 1:1 to 1:10.

[0073] The second lithium salt has an excellent ion transport effect, but may generate amine or alkali components due to a side reaction with moisture in the battery. Therefore, if the molar ratio of the second lithium salt relative to 1 mole of the first lithium salt is greater than 50, the metal component, for example, the current collector or the battery case, may be corroded by the amine or alkali components generated by the side reaction, or the cross-linking reaction rate between polymers during thermal polymerization may be reduced.

[0074] In the electrolyte for secondary batteries, the total concentration of lithium salts may be in the range of 0.1M to 5M, specifically 0.5M to 5M, and more specifically 1M to 4.5M. In the case where the total mixed concentration of lithium salts in the electrolyte for secondary batteries is less than 0.1M, the electrolyte performance is reduced due to the reduced ion conductivity of the electrolyte. If the mixed concentration of lithium salts is greater than 5M, the impregnation of the electrolyte is reduced due to the increased viscosity of the electrolyte, and the mobility of lithium ions may be reduced to reduce capacity characteristics.

[0075] (2) Non-aqueous organic solvents

[0076] Various organic solvents commonly used in lithium electrolytes may be used as the non-aqueous organic solvent without limitation. For example, the organic solvent may include a cyclic carbonate-based organic solvent, a linear carbonate-based organic solvent, or a mixed organic solvent thereof.

[0077] The cyclic carbonate-based organic solvent is a high-viscosity organic solvent that can well dissociate lithium salts in the electrolyte due to its high dielectric constant, wherein a specific example of the cyclic carbonate-based organic solvent can be at least one organic solvent selected from the following: ethylene carbonate (EC), propylene carbonate (PC), 1,2-butenyl carbonate, 2,3-butenyl carbonate, 1,2-pentenyl carbonate, 2,3-pentenyl carbonate, or vinylene carbonate, and, among them, the cyclic carbonate-based organic solvent can include at least one of ethylene carbonate and propylene carbonate (PC).

[0078] In addition, the linear carbonate-based organic solvent is an organic solvent having low viscosity and low dielectric constant, wherein a typical example thereof may be at least one organic solvent selected from the following: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dipropyl carbonate, methyl propyl carbonate, or ethyl propyl carbonate, and specifically may include at least one of dimethyl carbonate and ethyl methyl carbonate.

[0079] In addition, in the present disclosure, a mixture of a cyclic carbonate-based organic solvent and a linear carbonate-based organic solvent may be included, wherein the mixing ratio of the cyclic carbonate-based organic solvent and the linear carbonate-based organic solvent may be 10:90 to 50:50 by volume, and specifically 15:85 to 30:70 by volume to ensure high ionic conductivity.

[0080] In addition, the organic solvent may further include at least one of a linear ester-based organic solvent and a cyclic ester-based organic solvent, which has a lower melting point and higher high temperature stability than a cyclic carbonate-based organic solvent and / or a linear carbonate-based organic solvent to improve the ionic conductivity of the electrolyte. Specifically, the organic solvent may further include a linear ester-based organic solvent, which can reduce the viscosity of the electrolyte used in the secondary battery, and can simultaneously increase the degree of dissociation of the lithium salt by chelating the lithium cation through the ether symmetric structure. In the case of further using a linear ester-based solvent, the ionic conductivity of the electrolyte used in the secondary battery can be further improved.

[0081] Any one selected from methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate or a mixture of two or more thereof may be generally used as the linear ester-based organic solvent, but the linear ester-based organic solvent is not limited thereto.

[0082] In addition, the cyclic ester-based organic solvent may include at least one organic solvent selected from γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, or ε-caprolactone.

[0083] The remainder of the electrolyte for a secondary battery of the present disclosure except for the lithium salt, the polymer, and other additives may all be a non-aqueous organic solvent.

[0084] (3) Additives

[0085] The electrolyte for a secondary battery of the present disclosure may have a stable passivation capability on a positive electrode surface, and may include an additive capable of forming a film having a low interface resistance.

[0086] The additive may include a polymer or an oligomer including a repeating unit derived from a monomer represented by Formula 1 and a repeating unit derived from a monomer represented by Formula 2 below.

[0087] [Formula 1]

[0088]

[0089] In formula 1,

[0090] R is an alkylene group having 1 to 5 carbon atoms, and

[0091] R" is H or Li.

[0092] [Formula 2]

[0093]

[0094] In Formula 2,

[0095] R1 and R 2 Each is independently an alkylene group having 1 to 5 carbon atoms.

[0096] The polymer included as an additive of the present disclosure includes a repeating unit containing a cyano group (CN) that can easily form a coordination bond with a metal on the positive electrode surface or a metal ion dissolved from the positive electrode as an end group, and a repeating unit containing a hydroxyl group (-OH) having excellent adsorption capacity for transition metals on the positive electrode surface as an end group, as an essential component. In particular, the polymer of the present disclosure includes a methacrylate group as a main chain unit, thereby forming a more solid film with low fluidity on the electrode surface and capable of coordinating with lithium ions, thereby reducing the positive electrode interface resistance. Therefore, the present disclosure can achieve a lithium secondary battery that can reduce side reactions and ensure excellent high temperature durability and low temperature resistance properties.

[0097] In Formula 1 above, R may be an alkylene group having 1 to 4 carbon atoms, and R″ may be H. Specifically, R may be an alkylene group having 1 to 3 carbon atoms, and preferably, R may be an alkylene group having 1 carbon atom or 2 carbon atoms.

[0098] Furthermore, in the above formula 2, R 1 and R 2 Each may independently be an alkylene group having 1 to 4 carbon atoms, specifically, each may independently be an alkylene group having 2 or 3 carbon atoms, and preferably, each may independently be an unsubstituted alkylene group having 2 or 3 carbon atoms.

[0099] R, R 1 and R 2 It may be a group in which at least one hydrogen bonded to carbon is substituted with an element or group other than hydrogen, specifically, with an alkyl group having 1 to 5 carbon atoms.

[0100] Furthermore, the polymer of the present disclosure may additionally include a repeating unit derived from a monomer represented by Formula 3 below.

[0101] [Formula 3]

[0102]

[0103] In the above formula 3,

[0104] R' is an alkyl group having 1 to 6 carbon atoms.

[0105] The polymer of the present disclosure may further improve solubility in an organic solvent by including a repeating unit represented by the above Formula 3 containing an alkyl group (R′) as a terminal group.

[0106] In the above Formula 3, R′ may be an alkyl group having 1 to 5 carbon atoms, and preferably may be an alkyl group having 1 to 4 carbon atoms.

[0107] R' may be a group in which at least one hydrogen bonded to carbon is substituted with an element or group other than hydrogen, specifically, with an alkyl group having 1 to 5 carbon atoms.

[0108] The polymer of the present disclosure may include a unit represented by Formula 4 below.

[0109] [Formula 4]

[0110]

[0111] In the above formula 4,

[0112] R, R 1 and R 2 are each independently an alkylene group having 1 to 5 carbon atoms,

[0113] R' is an alkyl group having 1 to 6 carbon atoms,

[0114] R" is H or Li,

[0115] k is any integer from 1 to 15,000,

[0116] m is any integer from 10 to 12,000, and

[0117] n is an arbitrary integer from 10 to 8,500.

[0118] Specifically, the compound represented by Formula 4 may include a compound represented by the following Formula 4a.

[0119] [Formula 4a]

[0120]

[0121] In the above formula 4a,

[0122] R' is a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms,

[0123] R" is H or Li,

[0124] k is any integer from 1 to 15,000,

[0125] m is any integer from 10 to 12,000, and

[0126] n is an arbitrary integer from 10 to 8,500.

[0127] More specifically, the compound represented by Formula 4 may include a compound represented by the following Formula 4a-1 or Formula 4a-2.

[0128] [Formula 4a-1]

[0129]

[0130] In the above formula 4a-1,

[0131] k" is any integer from 1 to 15,000,

[0132] m" is any integer from 10 to 12,000, and

[0133] n" is an integer anywhere from 10 to 8,500.

[0134] [Formula 4a-2]

[0135]

[0136] In the above formula 4a-2,

[0137] k" is any integer from 1 to 15,000,

[0138] m" is any integer from 10 to 12,000, and

[0139] n" is an integer anywhere from 10 to 8,500.

[0140] In Formula 4 above, a molar ratio of repeating unit n to (repeating unit k+repeating unit m) may be in the range of 1:0.001 to 1:10, specifically 1:0.01 to 1:10, more specifically 1:0.05 to 1:10, and more specifically 1:0.2 to 1:8.

[0141] If, in the above formula 4, the molar ratio of (repeating unit k + repeating unit m) relative to 1 mol of repeating unit n is less than 0.001, it is difficult to form a stable electrolyte for a secondary battery because not only the lithium ion transmission efficiency is reduced, but also the cross-linking reaction rate of gelation is reduced. In addition, due to the reduced adhesion between the electrode and the separator, the effect of improving the stability to heat, machinery, and electrical shock may be negligible. In addition, in the above formula 4, if the molar ratio of (repeating unit k + repeating unit m) relative to 1 mol of repeating unit n is greater than 10, it may be difficult to control the gelation reaction rate.

[0142] In addition, a molar ratio of the repeating unit k:repeating unit m may be in the range of 1:0.01 to 1:10, specifically 1:0.02 to 1:9, and more specifically 1:0.02 to 1:5.

[0143] In the above formula 4, when the molar ratio of the repeating unit m relative to 1 mol of the repeating unit k is less than 0.1, the crosslinking reaction rate of gelation may be reduced. In addition, when the molar ratio of the repeating unit m relative to 1 mol of the repeating unit k is greater than 10, it may be difficult to control the gelation reaction rate.

[0144] The weight average molecular weight (Mw) of the polymer of the present disclosure can be controlled by the number of repeating units, and specifically can be in the range of 1,500,000 g / mol or less, more specifically 5,000 g / mol to 500,000 g / mol, and more specifically 5,000 g / mol to 400,000 g / mol.

[0145] When the weight average molecular weight of the polymer is within the above range, a crosslinking reaction can be performed even when heated at 60°C or higher without a polymerization initiator, and at the same time, the impregnation of the electrolyte for the secondary battery can be improved by controlling the viscosity of the electrolyte for the secondary battery. In particular, when the weight average molecular weight of the polymer is within the range of 5000 g / mol to 400000 g / mol, the electrolyte impregnation of the electrode and the separator can be further improved.

[0146] The weight average molecular weight of the polymer of the present disclosure can be measured by using gel permeation chromatography (GPC). For example, a sample with a predetermined concentration is prepared, and then the Alliance 4 as a GPC measurement system is stabilized. When the system is stabilized, a standard sample and the sample are injected into the system to obtain a chromatogram, and then the molecular weight can be calculated from the obtained results using an analytical method (system: Alliance 4, column: PL mixed B column of Agilent Technologies, eluent: tetrahydrofuran (THF), flow rate: 0.1 mL / min, temperature (temp): 40°C, injection volume (injection): 100 μL).

[0147] Furthermore, the viscosity of the polymer of the present disclosure may be in the range of 4.0 cPs to 100 cPs, more specifically 4.0 cPs to 20 cPs.

[0148] When the viscosity of the polymer of the present disclosure is within the above range, the impregnation property of the electrolyte can be more easily ensured. In this case, since it is difficult to ensure the impregnation of a large area and thick electrode when the viscosity of the polymer is 100 cPs or higher, in order to ensure that the impregnation of the electrolyte is within a certain range, it is desirable that the viscosity of the polymer is 100 cPs or lower.

[0149] After dissolving the polymer in a non-aqueous organic solvent at a concentration of 3 wt%, the viscosity was measured using a Brookfield LV DV-II+Pro viscometer (cone-plate type) at 25° C. During the measurement, the spindle was S40, the rotation speed was 15 rpm, and the sample loading amount was 1 mL.

[0150] Based on the total weight of the electrolyte for a secondary battery, the amount of the polymer in the present disclosure can be less than 55 wt%, for example, 0.1 wt% to 50 wt%, specifically 0.1 wt% to 30 wt%, more specifically 0.1 wt% to 20 wt%, and more specifically 0.1 wt% to 10 wt%.

[0151] If the amount of the polymer of the present disclosure is 0.1 wt % or more, not only the gel formation effect can be improved to ensure sufficient mechanical strength of the electrolyte for the secondary battery, but also an electrolyte for the secondary battery that can effectively control the side reaction with the positive electrode is formed, so that a strong film can be formed. In addition, if the amount of the polymer is less than 55 wt %, specifically 50 wt % or less, the side reaction and resistance increase caused by the excess polymer can be prevented, and the wetting properties of the electrolyte for the secondary battery can be improved. If the amount of the polymer in the electrolyte for the secondary battery is 55 wt % or more, the ionic conductivity is reduced due to the increase in viscosity, and the battery operating performance decreases, while the resistance increases. The electrolyte for the secondary battery of the present disclosure can form a liquid electrolyte or a (gel) polymer electrolyte depending on the content range of the polymer.

[0152] (4) Other additives

[0153] If necessary, other additives may be added to prevent the electrolyte for secondary batteries from decomposing and causing negative electrode collapse under high output conditions, or to further improve low-temperature high-rate discharge characteristics, high-temperature stability, overcharge protection, and battery expansion suppression effects at high temperatures.

[0154] Examples of these other additives may be at least one selected from the following: cyclic carbonate-based compounds, halogen-substituted carbonate-based compounds, sultone-based compounds, sulfate-based compounds, phosphate or phosphate ester-based compounds, borate or borate ester-based compounds, nitrile-based compounds, phenyl compounds, amine-based compounds, silane-based compounds, or lithium salt-based compounds.

[0155] The cyclic carbonate-based compound, for example, may include vinylene carbonate (VC) or vinyl ethylene carbonate.

[0156] The halogen-substituted carbonate-based compound, for example, may include fluoroethylene carbonate (FEC).

[0157] The sultone-based compound, for example, may include at least one selected from 1,3-propane sultone (PS), 1,4-butane sultone, ethane sultone, 1,3-propene sultone (PRS), 1,4-butene sultone, and 1-methyl-1,3-propene sultone.

[0158] The sulfate-based compound may include, for example, ethylene sulfate (Esa), trimethylene sulfate (TMS), or methyl trimethylene sulfate (MTMS).

[0159] The phosphate or phosphate-based compound, for example, may include at least one selected from the group consisting of lithium difluorobis(oxalato)phosphate, lithium difluorophosphate, tetramethyltrimethylsilylphosphate, trimethylsilylphosphate, or tris(2,2,2-trifluoroethyl)phosphate.

[0160] Borates or borate-based compounds, for example, may include tetraphenylborate and lithium oxalatodifluoroborate.

[0161] The nitrile compound, for example, may include at least one selected from the group consisting of succinonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, octanonitrile, heptanecarbonitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, benzyl cyanide, 2-fluorobenzonitrile, or 4-fluorobenzonitrile.

[0162] The phenyl compound, for example, may include fluorobenzene, the amine compound may include triethanolamine or ethylenediamine, and the silane compound may include tetravinylsilane.

[0163] The lithium salt-based compound is a compound different from the lithium salt included in the electrolyte of the present disclosure, wherein the lithium salt-based compound may include at least one selected from the following: LiPO 2 F 2 、LiODFB、LiBOB(Lithium bis(oxalato)borate(LiB(C 2 O 4 ) 2 )), or LiBF 4 .

[0164] In the case of including vinylene carbonate, vinyl ethylene carbonate, or succinonitrile among these other additives, a more robust solid electrolyte interface (SEI) may be formed on the negative electrode surface during the initial activation process of the secondary battery.

[0165] Including LiBF 4 In this case, the high temperature stability of the secondary battery can be improved by suppressing the generation of gas that may be generated by decomposition of the electrolyte during high temperature storage.

[0166] These other additives can be used as a mixture of two or more of them, and the amount of these other additives can be 0.01 wt % to 10 wt %, specifically 0.01 wt % to 8 wt %, and preferably 0.05 wt % to 5 wt % based on the total weight of the electrolyte for the secondary battery. If the amount of other additives is less than 0.01 wt %, the effect of improving the low temperature output, high temperature storage characteristics, and high temperature life characteristics of the battery is negligible, and if the amount of other additives is greater than 10 wt %, there is a possibility of excessive occurrence of side reactions during the charging and discharging of the battery due to excessive additives. In particular, due to excessive addition of additives for forming SEI, they may not be fully decomposed at high temperatures, unreacted materials may be formed in the electrolyte at room temperature, or additives for forming SEI may exist in the form of precipitates. Therefore, side reactions that reduce the life or resistance characteristics of the secondary battery may occur.

[0167] Lithium secondary battery

[0168] Furthermore, the present disclosure provides a lithium secondary battery including the electrolyte of the present disclosure.

[0169] The lithium secondary battery of the present disclosure can be prepared by the following steps: (a) housing an electrode assembly formed by sequentially stacking a positive electrode, a separator, and a negative electrode in a battery case; (b) injecting an electrolyte for a secondary battery of the present disclosure into the battery case; and (c) activating the electrolyte for a secondary battery at 25° C. to 100° C. to form an electrolyte film on the electrode surface.

[0170] In this case, the activation step may be performed for about 2 minutes to 48 hours, specifically 1 hour to 24 hours.

[0171] Activation is a step of forming a solid electrolyte interface (SEI) on the negative electrode surface by partial charging and discharging, which can be performed by methods known in the art. Specifically, for example, charging and discharging can be performed once or repeatedly within a predetermined range of constant current or constant voltage. Specifically, charging and discharging can be performed once within a voltage range of 2.5V to 4.8V. In addition, charging for activation can be performed within a state of charge (SOC) of 30% to 70%.

[0172] The method may further comprise aging after the activating step.

[0173] Aging The battery activated as described above is stabilized by leaving the battery for a predetermined period of time, wherein the aging may be performed at 19° C. to 25° C.

[0174] Those prepared by a typical method and used in the preparation of a lithium secondary battery may be used as the positive electrode, the negative electrode, and the separator used in the lithium secondary battery of the present disclosure without particular limitation.

[0175] (1) Positive electrode

[0176] The positive electrode according to the present disclosure may include a positive electrode active material layer including a positive electrode active material, and, if necessary, the positive electrode active material layer may further include a conductive agent and / or a binder.

[0177] A lithium iron phosphate-based positive electrode active material having a very stable structure can be used for the positive electrode active material.

[0178] The lithium iron phosphate-based positive electrode active material may be represented by Formula I below.

[0179] [Formula I]

[0180] LiFe 1-x M x PO 4

[0181] In the above formula I,

[0182] M is any one selected from Mn, Ni, Co, Cu, Sc, Ti, Cr, V, or Zn, wherein 0≤x<1.

[0183] In the above Formula I, M is a metal element capable of improving the structural stability and conductivity of the lithium iron phosphate-based positive active material by replacing Fe, and specifically, may include any one, or two or more elements selected from Ni, Co, or Mn.

[0184] In the above formula I, x may be 0≤x≤0.5.

[0185] Lithium iron phosphate-based positive electrode active materials, in particular, LiFePO with an olivine structure 4 , with 3.6g / cm 3 The high volume density of LiFePO4 can produce a high potential of 3.4V and has a high theoretical capacity of about 170mAh / g. 4 It contains electrochemically undoped Li at a ratio of one Li atom per Fe atom and is therefore a promising material as a positive electrode active material for secondary batteries.4 It has low bulk ionic conductivity and low electrical conductivity, which results in low output characteristics due to high interface resistance on the surface. In particular, it has a disadvantage that Fe ions originating from Fe oxide-based impurities are dissolved into the electrolyte and then precipitated on the negative electrode surface.

[0186] The present invention uses an electrolyte including a polymer containing a cyano group (CN) as an end group as an additive to form a coordination bond with the metal ions dissolved from the positive electrode, thereby increasing the effect of removing the metal ions, and at the same time, the dissolution of the metal ions can be effectively suppressed by forming a functional polymer layer (film) on the surface of the positive electrode. Therefore, the side reaction caused by the dissolved metal ions can be solved.

[0187] As the positive electrode active material of the present disclosure, if necessary, in addition to the lithium iron phosphate-based positive electrode active material, a lithium nickel cobalt manganese-based oxide represented by the following Formula II may be further used together:

[0188] [Formula II]

[0189] Li x [Ni y Co z Mn w M 1 v ]O 2

[0190] In Formula II,

[0191] M 1 It is a doping element that replaces the transition metal site and may include at least one element selected from the following: W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, or Mo, where y+z+w+v=1.

[0192] x represents the atomic ratio of lithium to the total transition metal in the lithium nickel cobalt manganese-based oxide, wherein x may be in the range of 0.8 to 1.2, and preferably 1 to 1.2.

[0193] y represents the atomic ratio of nickel in the transition metal in the lithium nickel cobalt manganese-based oxide, wherein y is in the range of 0.5 or more to less than 1, preferably 0.7 to less than 1, and more preferably 0.75 to 0.98. Since a higher capacity can be achieved as the amount of nickel in the transition metal increases, an amount of nickel of 0.5 or more is more advantageous for achieving a high capacity.

[0194] z represents the atomic ratio of cobalt in the transition metal in the lithium nickel cobalt manganese-based oxide, wherein z is in the range of more than 0 to 0.5 or less, preferably 0.01 to 0.3, and more preferably 0.01 to 0.25.

[0195] w represents an atomic ratio of manganese in transition metals in the lithium nickel cobalt manganese-based oxide, wherein w is in the range of more than 0 to 0.5 or less, preferably 0.01 to 0.3, and more preferably 0.01 to 0.25.

[0196] v represents the doping element M doped into the transition metal site in the lithium nickel cobalt manganese-based oxide 1 The atomic ratio of wherein v may be in the range of 0 to 0.2, preferably 0 to 0.1. 1 In the case of , there is an effect of improving the structural stability of the lithium nickel cobalt manganese-based oxide, but since the capacity may decrease when the content of the doping element increases, it is desirable that the amount of the doping element is 0.2 or less.

[0197] A specific example of lithium nickel cobalt manganese-based oxide may be LiNi 0.5 Co 0.2 Mn 0.3 O 2 、Li(Ni 0.5 Mn 0.3 Co 0.2 ) 2 、Li(Ni 0.6 Mn 0.2 Co 0.2 ) 2 、Li(Ni 0.7 Mn 0.15 Co 0.15 ) 2 , or Li(Ni 0.8 Mn 0.1 Co 0.1 ) 2 , but not limited to this.

[0198] The amount of the positive electrode active material may be 80 wt % to 98 wt %, more specifically 85 wt % to 98 wt % based on the total weight of the positive electrode active material layer. When the amount of the positive electrode active material is within the above range, excellent capacity characteristics may be exhibited.

[0199] Next, the conductive agent can be used to provide conductivity to the electrode, and there is no particular limitation as long as it has conductivity and does not cause adverse chemical changes in the battery. Specific examples thereof are conductive materials such as: graphite such as natural graphite or artificial graphite; carbon black such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as copper, nickel, aluminum, silver, etc.; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or polyphenylene derivatives, and any one of them or a mixture of two or more of them can be used.

[0200] The conductive agent may be added in an amount of 0.1 wt % to 10 wt %, preferably 0.1 wt % to 5 wt %, based on the total weight of the positive electrode active material layer.

[0201] The binder improves adhesion between positive electrode active material particles and adhesion between the positive electrode active material and the current collector.

[0202] Examples of binders may include fluororesin-based binders, including polyvinylidenefluoride (PVDF) or polytetrafluoroethylene (PTFE); rubber-based binders, including styrene butadiene rubber (SBR), acrylonitrile-butadiene rubber, or styrene-isoprene rubber; cellulose-based binders, including carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, or regenerated cellulose; polyol-based binders, including polyvinyl alcohol; polyolefin-based binders, including polyethylene or polypropylene; polyimide-based binders; polyester-based binders; and silane-based binders, and any one of them or a mixture of two or more of them may be used. The binder is generally added in an amount of 0.1% to 15% by weight, preferably 0.1% to 10% by weight, based on the total weight of the positive electrode active material layer.

[0203] The positive electrode of the present invention as described above can be prepared by a method for preparing a positive electrode known in the art. For example, the positive electrode can be prepared by the following method: the positive electrode current collector is coated with a positive electrode slurry prepared by dissolving or dispersing a positive electrode active material, a binder, and / or a conductive agent in a solvent, rolled and dried, or can be prepared by casting a positive electrode active material layer on a separate carrier and then laminating the film separated from the carrier on the positive electrode current collector.

[0204] There is no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and, for example, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, or the like can be used. In addition, the thickness of the positive electrode current collector can generally be 3 μm to 500 μm, and microscopic random bodies can be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. The positive electrode current collector, for example, can be used in various shapes such as films, sheets, foils, nets, porous bodies, foams, non-woven objects, etc.

[0205] The solvent may be a commonly used solvent in the art, and may include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and any one of them or a mixture of two or more of them may be used. If the positive electrode material mixture is adjusted to have a suitable viscosity in consideration of the coating thickness, manufacturing yield, and processability of the positive electrode material mixture, the amount of the solvent used may be sufficient, and there is no particular limitation.

[0206] (2) Negative electrode

[0207] Next, the negative electrode will be described.

[0208] The negative electrode according to the present disclosure includes a negative electrode active material layer including a negative electrode active material, and, if necessary, the negative electrode active material layer may further include a conductive agent and / or a binder.

[0209] As the negative electrode active material, various negative electrode active materials known in the art may be used, for example, a carbon-based negative electrode active material, a silicon-based negative electrode active material, or a mixture thereof.

[0210] According to one embodiment, the negative electrode active material may include a carbon-based negative electrode active material, and as the carbon-based negative electrode active material, various carbon-based negative electrode active materials used in the art may be used, for example, graphite-based materials such as natural graphite, artificial graphite, Kishi graphite; pyrolytic carbon; mesophase pitch based carbon fiber; meso-carbon microbeads; mesophase pitches; high-temperature calcined carbon such as petroleum or coal tar pitch derived cokes; soft carbon; and hard carbon. The shape of the carbon-based negative electrode active material is not particularly limited, and materials having various shapes such as irregular shapes, planar shapes, flaky shapes, spherical shapes, or fibrous shapes may be used.

[0211] Preferably, the carbon-based negative electrode active material may include at least one of natural graphite and artificial graphite. More preferably, the carbon-based negative electrode active material may include natural graphite and artificial graphite. When natural graphite and artificial graphite are used together, the adhesion to the current collector can be improved to suppress the peeling of the active material.

[0212] According to another embodiment, the negative electrode active material may include a silicon-based negative electrode active material. The silicon-based negative electrode active material may include, for example, at least one selected from metallic silicon (Si), silicon oxide (SiOx, 0 < x ≤ 2), silicon carbide (SiC), or a Si-Y alloy (where Y is an element selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements, transition metals, rare earth elements, or a combination thereof and is not Si). The element Y may be selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a combination thereof.

[0213] Since the silicon-based negative electrode active material has higher capacity characteristics than the carbon-based negative electrode active material, better capacity characteristics can be obtained when the silicon-based negative electrode active material is further included. However, compared with the graphite negative electrode, the negative electrode including the silicon-based negative electrode active material contains more O-rich components in the SEI, and the SEI containing the O-rich component is in, for example, HF or PF5 Lewis acids such as HF and PF tend to decompose more easily when present in the electrolyte. Therefore, for the negative electrode including the silicon-based negative electrode active material, it is necessary to suppress the 5 The nonaqueous electrolyte according to the present invention includes a compound represented by formula II containing a N atom acting as a Lewis base and a F atom improving the stability of the SEI on the negative electrode surface as an additive, so that the decomposition of the SEI can be effectively suppressed when using a negative electrode including a silicon-based negative electrode active material.

[0214] According to another embodiment, the negative electrode active material may include a mixture of a carbon-based negative electrode active material and a silicon-based negative electrode active material.

[0215] Specific examples of the carbon-based negative electrode active material and the silicon-based negative electrode active material are the same as described above.

[0216] The mixing ratio of the silicon-based negative electrode active material to the carbon-based negative electrode active material may be in the range of 3:97 to 99:1, preferably 5:95 to 30:70, and more preferably 5:95 to 15:85 as a weight ratio. In the case where the mixing ratio of the silicon-based negative electrode active material to the carbon-based negative electrode active material satisfies the above range, since the volume expansion of the silicon-based negative electrode active material is suppressed while the capacity characteristics are improved, excellent cycle performance can be ensured.

[0217] The amount of the negative electrode active material may be 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer. When the amount of the negative electrode active material satisfies the above range, excellent capacity characteristics and electrochemical properties may be obtained.

[0218] Next, the conductive agent is a component that further improves the conductivity of the negative electrode active material, wherein the conductive agent can be added in an amount of 10 wt % or less, preferably 5 wt % or less based on the total weight of the negative electrode active material layer. Any conductive agent can be used without particular limitation as long as it has conductivity and does not cause adverse chemical changes in the battery, and, for example, conductive materials such as: graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as copper powder, nickel powder, aluminum powder, silver powder, etc.; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or polyphenylene derivatives.

[0219] The binder is a component that assists the conductive agent, the active material, and the current collector, wherein the binder is generally added in an amount of 0.1 wt % to 10 wt % based on the total weight of the negative electrode active material layer. Examples of binders may be fluororesin-based binders, including polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); rubber-based binders, including styrenebutadiene rubber (SBR), acrylonitrile-butadiene rubber, or styrene-isoprene rubber; cellulose-based binders, including carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, or regenerated cellulose; polyol-based binders, including polyvinyl alcohol; polyolefin-based binders, including polyethylene or polypropylene; polyimide-based binders; polyester-based binders; and silane-based binders.

[0220] The negative electrode can be prepared by a method for preparing a negative electrode known in the art. For example, the negative electrode can be prepared by coating the negative electrode current collector with a negative electrode slurry prepared by dissolving or dispersing the negative electrode active material, and optionally a binder and a conductive agent in a solvent, rolling and drying to form a negative electrode active material layer, or by casting the negative electrode active material layer on a separate carrier and then laminating the film separated from the carrier on the negative electrode current collector.

[0221] The thickness of the negative electrode current collector may generally be 3 μm to 500 μm.

[0222] The negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause adverse chemical changes in the battery, and, for example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, or copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, or the like can be used. In addition, similar to the positive electrode current collector, microscopic random bodies can be formed on the surface of the current collector to improve the adhesion of the negative electrode active material. The negative electrode current collector, for example, can be used in various shapes such as films, sheets, foils, nets, porous bodies, foams, non-woven objects, etc.

[0223] The solvent may be a commonly used solvent in the art, and may include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and any one of them or a mixture of two or more of them may be used. If the negative electrode slurry can be adjusted to have a suitable viscosity in consideration of the coating thickness, manufacturing yield, and processability of the negative electrode material mixture, the amount of the solvent used may be sufficient and is not particularly limited.

[0224] (3) Partition

[0225] In addition, the separator functions to prevent internal short circuits between two electrodes and is impregnated with an electrolyte, wherein, after mixing a polymer resin, a filler, and a solvent to prepare a separator composition, the separator composition is directly coated on the electrode and dried to form a separator film, or, after the separator composition is cast on a support and dried, the separator can be prepared by laminating the separator film separated from the support on the electrode surface.

[0226] A commonly used porous polymer film, for example, a porous polymer film prepared from a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer can be used as a separator alone or in the form of a laminate thereof. In addition, a typical porous nonwoven fabric, for example, a nonwoven fabric formed from a high melting point glass fiber or a polyethylene terephthalate fiber can be used, but is not limited thereto.

[0227] In this case, the porous separator may generally have a pore diameter of 0.01 μm to 50 μm and a porosity of 5% to 95%. In addition, the porous separator may generally have a thickness of 5 μm to 300 μm.

[0228] The shape of the lithium secondary battery of the present disclosure is not particularly limited, but a cylindrical type using a can, a prismatic type, a pouch type, or a coin type may be used.

[0229] Example

[0230] Example 1.

[0231] (Preparation of electrolyte for secondary battery)

[0232] In LiPF 6 LiPF was dissolved in a non-aqueous organic solvent in which ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 30:40:30. 6After the concentration is 1.0 M, an electrolyte for a secondary battery is prepared by adding 0.5 wt % of a polymer represented by Formula 4a-1 (the molar ratio of k":m":n" is 25:20:55, and the weight average molecular weight (Mw) is 15,000), 2.5 wt % of vinylene carbonate (VC), and 0.5 wt % of 1,3-propane sultone.

[0233] (Secondary Battery Preparation)

[0234] The positive electrode active material (LiFePO 4 ), a conductive agent (carbon black), and a binder (polyvinylidene fluoride: PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 94:3:3 to prepare a positive electrode active material slurry (solid content 48 wt%). A 100 μm thick positive electrode current collector (aluminum film) was coated with the positive electrode active material slurry, dried, and roll-pressed to prepare a positive electrode.

[0235] The negative electrode active material (carbon powder), binder (PVDF), and conductive agent (carbon black) were added to NMP as a solvent at a weight ratio of 96:3:1 to prepare a negative electrode active material slurry (solid content: 70 wt %). A 90 μm thick negative electrode current collector (copper thin film) was coated with the negative electrode active material slurry, dried, and rolled to prepare a negative electrode.

[0236] After preparing an electrode assembly by sequentially stacking the positive electrode, the negative electrode, and a separator having three layers of polypropylene / polyethylene / polypropylene (PP / PE / PP), the electrode assembly is placed in a pouch-type secondary battery case, and the electrolyte for a secondary battery prepared above is injected and heat-treated at 60°C for 1 hour to prepare a lithium secondary battery including the electrolyte for a secondary battery.

[0237] Example 2.

[0238] (Preparation of electrolyte for secondary battery)

[0239] In LiPF 6 LiPF was dissolved in a non-aqueous organic solvent in which ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 30:40:30. 6 After the concentration of is 1.0 M, an electrolyte for a secondary battery is prepared by adding 1.0 wt % of a polymer represented by Formula 4a-1 (the molar ratio of k":m":n is 25:20:55, and the weight average molecular weight (Mw) is 15,000), 2.5 wt % of vinylene carbonate (VC), and 0.5 wt % of 1,3-propane sultone.

[0240] (Secondary Battery Preparation)

[0241] A lithium secondary battery was prepared in the same manner as in Example 1, except that the electrolyte for a secondary battery prepared above was used.

[0242] Example 3.

[0243] (Preparation of electrolyte for secondary battery)

[0244] In LiPF 6 LiPF was dissolved in a non-aqueous organic solvent in which ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 30:40:30. 6 After the concentration is 1.0 M, an electrolyte for a secondary battery is prepared by adding 2.0 wt % of a polymer represented by Formula 4a-1 (the molar ratio of k":m":n is 25:20:55, and the weight average molecular weight (Mw) is 15,000), 2.5 wt % of vinylene carbonate (VC), and 0.5 wt % of 1,3-propane sultone.

[0245] (Secondary Battery Preparation)

[0246] A lithium secondary battery was prepared in the same manner as in Example 1, except that the electrolyte for a secondary battery prepared above was used.

[0247] Example 4.

[0248] (Preparation of electrolyte for secondary battery)

[0249] In LiPF 6 LiPF was dissolved in a non-aqueous organic solvent in which ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 30:40:30. 6 After the concentration is 1.0 M, an electrolyte for a secondary battery is prepared by adding 1.0 wt % of a polymer represented by Formula 4a-2 (the molar ratio of k":m":n is 25:20:55, and the weight average molecular weight (Mw) is 16,000), 2.5 wt % of vinylene carbonate (VC), and 0.5 wt % of 1,3-propane sultone.

[0250] (Secondary Battery Preparation)

[0251] A lithium secondary battery was prepared in the same manner as in Example 1, except that the electrolyte for a secondary battery prepared above was used.

[0252] Comparative Example 1.

[0253] (Preparation of electrolyte for secondary battery)

[0254] In LiPF 6 LiPF was dissolved in a non-aqueous organic solvent in which ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 30:40:30. 6 After the concentration of MgSO4 was 1.0 M, an electrolyte for a secondary battery was prepared by adding 2.5 wt % of vinylene carbonate (VC) and 0.5 wt % of 1,3-propane sultone.

[0255] (Secondary Battery Preparation)

[0256] A lithium secondary battery was prepared in the same manner as in Example 1, except that the electrolyte for a secondary battery prepared above was used.

[0257] Comparative Example 2.

[0258] (Preparation of electrolyte for secondary battery)

[0259] In LiPF 6 LiPF was dissolved in a non-aqueous organic solvent in which ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 30:40:30. 6 After the concentration of was 1.0 M, an electrolyte for a secondary battery was prepared by adding 0.5 wt % of a polymer represented by Formula 5 (the molar ratio of o:p:q was 30:1:59 and the weight average molecular weight (Mw) was 51,000), 2.5 wt % of vinylene carbonate (VC), and 0.5 wt % of 1,3-propane sultone.

[0260] (Secondary Battery Preparation)

[0261] A lithium secondary battery was prepared in the same manner as in Example 1, except that the electrolyte for a secondary battery prepared above was used.

[0262] [Formula 5]

[0263]

[0264] Experimental example

[0265] Experimental Example 1. Evaluation of resistance increase rate after high temperature cycling

[0266] After the secondary battery prepared in Example 1 and the secondary batteries prepared in Comparative Examples 1 and 2 were charged at a 0.33C rate under constant current / constant voltage conditions at room temperature (25°C) and discharged at a 0.33C rate for 10 seconds, the initial resistance was measured by using a PNE-0506 charging / discharging device (manufacturer: PNE solution), and the results are presented in the following Table 1.

[0267] Next, each secondary battery was charged to 3.20V at a rate of 0.33C under constant current-constant voltage (CC-CV) conditions at high temperature (45°C), and then discharged to 2.5V at a rate of 0.33C under constant current (CC) conditions, which was set as one cycle. After 300 cycles of charge and discharge, the resistance was measured, and then the resistance increase rate (%) was calculated by using the following formula 1. The calculated resistance increase rate (%) is shown in the following Table 1.

[0268] [Formula 1]

[0269] Resistance increase rate (%) = {(resistance after 300 cycles - initial resistance) / initial resistance} × 100

[0270] Experimental Example 2. Evaluation of Capacity Retention after High-Temperature Cycling

[0271] After the secondary battery prepared in Example 1 and the secondary batteries prepared in Comparative Examples 1 and 2 were charged at a 0.33C rate under constant current / constant voltage conditions at room temperature (25° C.) and discharged at a 0.33C rate for 10 seconds, the initial discharge capacity was measured by using a PNE-0506 charge / discharge apparatus (manufacturer: PNE solution).

[0272] Next, each secondary battery was charged to 3.20V at a rate of 0.33C under constant current-constant voltage (CC-CV) conditions at high temperature (45°C), and then discharged to 2.5V at a rate of 0.33C under constant current (CC) conditions, which was set as one cycle. After 300 cycles of charge and discharge, the discharge capacity was measured, and then the capacity retention rate (%) was calculated by using the following formula 2. The calculated capacity retention rate (%) is shown in Table 1 below.

[0273] [Formula 2]

[0274] Capacity retention rate (%) = (discharge capacity after 300 cycles / initial discharge capacity) × 100

[0275] [Table 1]

[0276]

[0277] Referring to Table 1, it can be understood that the resistance increase rate (%) and capacity retention rate (%) of the secondary battery of Example 1 are improved compared with the secondary batteries prepared in Comparative Examples 1 and 2 after 300 cycles at high temperature.

[0278] Experimental Example 3. Evaluation of Metal Dissolution Amount

[0279] After the secondary battery of Example 1 and the secondary batteries of Comparative Examples 1 and 2 that completed the cycle characteristic evaluation in Experimental Example 2 were disassembled to recover the positive electrode plate, each was sealed in 20 mL of the electrolyte prepared in Example 1 and stored in an oven at 45° C. for 1 week.

[0280] Then, the electrolyte was recovered, and the amount of the eluted transition metal (Fe) was measured by ICP analysis, and the results are shown in Table 2 below.

[0281] [Table 2]

[0282] Fe dissolution amount (ppm) Example 1 154 Comparative Example 1 375 Comparative Example 2 182

[0283] Referring to Table 2, it can be understood that the amount of the eluted transition metal of the secondary battery of Example 1 is decreased compared to the secondary batteries prepared in Comparative Examples 1 and 2.

[0284] Experimental Example 4. Evaluation of Low-temperature Discharge Capacity

[0285] After the secondary batteries prepared in Examples 1 to 4 and the secondary batteries prepared in Comparative Examples 1 and 2 were charged at a 0.33C rate under constant current / constant voltage conditions at room temperature (25°C) and discharged at a 0.33C rate for 10 seconds, the initial discharge capacity was measured by using a PNE-0506 charge / discharge device (25°C) (manufacturer: PNE solution).

[0286] Next, after these batteries were placed at low temperature (-20°C) for 3 hours, and these batteries were charged to 3.2V at 1C rate under constant current / constant voltage conditions, and discharged to 2.5V at 1C rate under constant current conditions, and the discharge capacity retention rate at low temperature was measured. The results are presented in Table 3 below. At this time, based on the low-temperature discharge capacity retention rate (%) of the lithium secondary battery of Comparative Example 1, the low-temperature discharge capacity retention rate (%) of the secondary batteries in Examples 1 to 4 and Comparative Example 2 was converted into a relative ratio, and the results are shown in Table 3 below.

[0287] [Table 3]

[0288] Low temperature discharge capacity retention rate (%) Example 1 113.3 Example 2 114.5 Example 3 115.4 Example 4 114.8 Comparative Example 1 - Comparative Example 2 108.2

[0289] Referring to Table 3, it can be understood that the low-temperature discharge capacity retention ratio (%) of the secondary batteries of Examples 1 to 4 of the present disclosure is improved compared to the secondary battery of Comparative Example 2.

Claims

1. An electrolyte for a secondary battery, comprising: Lithium salts; Non-aqueous organic solvents; and A polymer comprising a repeating unit derived from a monomer represented by Formula 1 and a repeating unit derived from a monomer represented by Formula 2; [Formula 1] In formula 1, R is an alkylene group having 1 to 5 carbon atoms, and R" is H or Li. [Formula 2] In Formula 2, R1 and R2 are each independently an alkylene group having 1 to 5 carbon atoms.

2. The electrolyte for a secondary battery according to claim 1, The lithium salt comprises LiPF6.

3. The electrolyte for a secondary battery according to claim 2, The lithium salt further comprises at least one selected from the group consisting of LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10 , LiAlCl4, LiAlO4, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiTFSI (lithium (bis)trifluoromethanesulfonimide, LiN(SO2CF3)2), LiFSI (lithium bis(fluorosulfonyl)imide, LiN(SO2F)2)), or LiBETI (lithium bisperfluoroethanesulfonimide, LiN(SO2CF2CF3)2)).

4. The electrolyte for a secondary battery according to claim 1, Wherein in Formula 1, R is an alkylene group having 1 to 4 carbon atoms, and R" is H.

5. The electrolyte for a secondary battery according to claim 1, Wherein in Formula 1, R is an alkylene group having 1 to 3 carbon atoms.

6. The electrolyte for a secondary battery according to claim 1, In Formula 1, R is an alkylene group having 1 carbon atom or 2 carbon atoms.

7. The electrolyte for a secondary battery according to claim 1, Wherein in Formula 2, R1 and R2 are each independently an alkylene group having 1 to 4 carbon atoms.

8. The electrolyte for a secondary battery according to claim 1, In Formula 2, R1 and R2 are each independently an alkylene group having 2 carbon atoms or 3 carbon atoms.

9. The electrolyte for a secondary battery according to claim 1, wherein the polymer further comprises a repeating unit derived from a monomer represented by Formula 3; [Formula 3] In formula 3, R' is an alkyl group having 1 to 6 carbon atoms.

10. The electrolyte for a secondary battery according to claim 9, Wherein in Formula 3, R' is an alkyl group having 1 to 5 carbon atoms.

11. The electrolyte for a secondary battery according to claim 9, Wherein in Formula 3, R' is an alkyl group having 1 to 4 carbon atoms.

12. The electrolyte for a secondary battery according to claim 1, wherein the polymer includes a unit represented by Formula 4; [Formula 4] In formula 4, R, R1 and R2 are each independently an alkylene group having 1 to 5 carbon atoms, R' is an alkyl group having 1 to 6 carbon atoms, R" is H or Li, k is any integer from 1 to 15,000, m is any integer from 10 to 12,000, and n is an arbitrary integer from 10 to 8,500.

13. The electrolyte for a secondary battery according to claim 1, The amount of the polymer is 0.1 wt% to 50 wt%. 14 . A lithium secondary battery comprising a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and the electrolyte for a secondary battery according to claim 1 .

15. The lithium secondary battery according to claim 14, The positive electrode comprises a lithium iron phosphate-based positive electrode active material represented by Formula I: [Formula I] LiFe 1-x M x PO4 (wherein in Formula I, M is any one selected from Mn, Ni, Co, Cu, Sc, Ti, Cr, V, or Zn, wherein 0≤x<1).

Citation Information

Patent Citations

  • Apparatus and method for inspecting dropped stated of ink droplet and methond

    KR1020220097614A

  • Power cable finishin apparatus and method

    KR1020230101238A